Silymarin administration after cerebral ischemia improves survival of obese mice by increasing cortical BDNF and IGF1 levels - Rodríguez-Cortés, Yesica María; Ramírez-Carreto, Ricardo Jair; Rodríguez-Barrena, Julia Isabel; Salazar-Castro, Marelly; Chavarría, Anahí (Frontiers in Aging Neuroscience, 2024)
BackgroundObesity is associated with a systemic inflammatory state that contributes to neuroinflammation and increases the risk of stroke at an early age. Stroke is the third leading cause of death worldwide and the leading cause of permanent disability. This work aimed to assess whether obesity-induced neuroinflammation can be a prognostic stroke factor that can be improved with oral administration of silymarin, an anti-inflammatory and neuroprotective drug.MethodsMale C57/Bl6 mice were used to establish an obesity model through a high-fat diet (HFD) for 12 weeks. Cerebral ischemia was performed with photothrombosis in the left motor cortex at the end of the diet. Following the induction of ischemia, silymarin (100 mg/kg) was administered orally for 14 days. Levels of pro-inflammatory (IL1β, TNFα, and MCP1) and anti-inflammatory markers (IL4, IL10), neurotrophic factors (IGF1, BDNF), and CX3CL1 were assessed in the cortex and striatum using ELISA.ResultsMice on the HFD gained significantly more weight than control subjects and exhibited altered glucose metabolism, which was improved after silymarin treatment. The survival rate was significantly lower in HFD mice (52.2%) compared to control mice (86%). Silymarin treatment improved survival in both ischemic groups (non-diet control: 95.7%, HFD: 78.3%). Silymarin raised cortical TNFα, IL4, IL10, IGF1, BDNF, and CX3CL1 levels in the HFD group with stroke, while the striatum did not present relevant differences.ConclusionOur findings suggest that silymarin improves glucose metabolism, possibly impacting post-stroke survival in obese mice. The increased levels of neurotrophic factors BDNF and IGF1, along with microglial regulatory factor CX3CL1, may contribute to the improved survival observed. These results indicate that silymarin could be a potential therapeutic option for managing neuroinflammation and enhancing post-stroke outcomes in obese individuals.